Eating Behaviors and Physical Activity Associated With Stress, Anxiety, and Depression During the COVID-19 Pandemic - Medina-Guillen, Leonardo Flavio (2022)
Introduction. Confinement was implemented as a preventive measure to limit contagion in the face of the COVID-19 pandemic. This measure limited food availability and favored the consumption of less healthy processed and non-perishable foods. These behaviors can be seen as related to mental health disorders, such as stress, anxiety, and depression. Methods. It is a quantitative, descriptive, cross-sectional study with non-probabilistic convenience sampling carried out between August-October 2020, with the participation of 1657 Latin American people from the general population. The Depression, Anxiety and Stress Scales-21 questionnaire and the eating behaviors questionnaire associated with stress, anxiety, and depression-17 were applied. Ordinal logistic regression was used to assess the association between variables. Results. The 62% of participants presented some degree of depression; 55.9%, anxiety; and 55.2%, stress. An association was found between stress with physical activity (p 0.048) and consumption of fish (p 0.041), water (p 0.003), breads / desserts (p 0.005), fast foods (p <0.001), sugary drinks (p 0.035), tea and infusions (p 0.023), and cocoa and its derivatives (p 0.018). Another association was also found between anxiety with physical activity (p 0.006) and intake of vegetables (p 0.022), fish (p 0.031), oils (p 0.008), breads / desserts (p 0.026), fast foods (p <0.001), tea and infusions (p 0.018), cocoa and derivatives (p 0.038), and vitamin supplements (p 0.016). Depression was also found as associated with physical activity (p 0.037) and consumption of fruits (p 0.012), water (p 0.012), coffee (p 0.045), breads / desserts (p 0.003), and fast foods (p <0.001). Conclusions. An association was found between consuming certain foods and high levels of stress, anxiety, and depression.